2021
DOI: 10.3892/etm.2021.10872
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of using exosome‑derived cysteine‑rich protein 61 as biomarkers for acute coronary syndrome

Abstract: Acute coronary syndrome (ACS) is the main manifestation of cardiovascular disease and the primary cause of adult hospitalization in China. There is an urgent demand for novel biomarkers for the diagnosis of ACS. Although plasma cysteine-rich protein 61 (Cyr61) has been previously reported to be accurate for ACS diagnosis, the accuracy of exosomal Cyr61 in ACS diagnosis remains unknown. In the present study, the aim was to assess the potential of applying exosomal Cyr61 in ACS diagnosis and to explore the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Li et al . showed that the elevated amount of CYR61 in circulating EVs is associated with acute coronary syndrome 56 . Besides, the level of Gap junction alpha-1 protein, also known as Connexin-43 (GJA1, CX43) is decreased in circulating and CM EVs after myocardial infarction 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Li et al . showed that the elevated amount of CYR61 in circulating EVs is associated with acute coronary syndrome 56 . Besides, the level of Gap junction alpha-1 protein, also known as Connexin-43 (GJA1, CX43) is decreased in circulating and CM EVs after myocardial infarction 57 .…”
Section: Discussionmentioning
confidence: 99%
“… 225 Li et al. 226 also found that increased expression of plasma exosome‐derived cysteine‐rich protein 61 (Cyr61) was associated with the acute coronary syndrome (ACS) and could be used in the diagnosis and prognosis of ACS. In addition, observation of urinary UMOD levels can be used as an early diagnostic biomarker for myocardial infarction.…”
Section: Exosome Biomarkersmentioning
confidence: 99%
“…The sensitivity of invasive CTA detection reaches 0.92 (sensitivity 92%, specificity 75%), but the sensitivity and specificity of other methods are poor (e.g., hs-cTnT, sensitivity 66.7%, specificity 84.2%). The detection ability and diagnostic efficacy of noncoding RNA (ncRNAs) and exosomes for CAD (e.g., Exos-Cyr61, sensitivity 48–57.5%, specificity 92–94%) are greater than those for ECG (sensitivity 29%, specificity 67%) and close to or higher than those with the Holter test (sensitivity 65%, specificity 90%) and transthoracic echocardiography (sensitivity 79%, specificity 80%) . It is reported that the sensitivity of exo-miR-942-5p, exo-miR-149-5p, and exo-miR-32-5p reaches 70–85% and the specificity reaches 62–85.7% .…”
Section: Exosomes As Diagnostic Markers In the Cardiovascular Systemmentioning
confidence: 99%